Measuring Awareness of the Importance of Green Computing Among Indonesian Senior High School Students: A Sample Study of One School - Rio Rinaldi; Fayyaz Haqqani; Dhafa Hibrizi Sitorus (Prosiding Seminar Nasional Ilmu Komputer, Sosial Sains, Teknik dan Multi-Disiplin Ilmu, 2025)
Green computing socialization was conducted at SMK Muhammadiyah 8 Medan on May 31, 2025, to enhance student awareness regarding environmentally friendly technology practices. The primary issue addressed was the need to build a collective responsibility towards the environment within the school's digital culture. The purpose of this study is to measure the level of student awareness and evaluate the effectiveness of the education program which utilized lectures, demonstrations, and interactive discussions. The research method used is descriptive with a participatory approach, collecting data through observation and questionnaires. The results indicated a significant improvement in understanding among the 27 participants, with 8 participants responding "very understood" and 14 participants responding "understood" regarding the material. The activity had a positive impact, fostering enthusiasm for applying energy-saving principles in daily life. These findings highlight the potential of green computing education to form a generation that is not only academically competent but also ecologically responsible.